Motivasi Orangtua/Wali Murid Sd Muhammadiyah Program Khusus Nogosari Memilih Sekolah Berbasis Kurikulum Syariah - Rahmawati, Syarifah Erma, Nur Amalia, S.S., M. Teach (2017)
The study has three aims. 1) Mentioning the factors of parents' intrinsic motivation in choosing syariah based curriculum school, 2) Mentioning the factors of parents' extrinsic motivation choosing the syariah based curriculum school, 3) the parents expectation after the children graduated from the school syariah based curriculum, SD Muhammadiyah Program Khusus Tinawas, Nogosari. The study used descriptive qualitative approach with phenomenology research design. The data were collected by interview, observation and documentation. The test of data validation used triangulation source and technique. The analyzing data is by reducing the data , presenting the data, and drawing conclusion. The result of study explain about the factors that cause the parents motivated in choosing the syariah based curriculum school SD Muhammadiyah Program Khusus Nogosari consisting intrinsic factors, and extrinsic factors. The intrinsic factors that cause the parents to be motivated for choosing the syariah based curriculum school SD Muhammadiyah Program Khusus Tinawas, Nogosari are: (1) The willing to have the sholeh and sholehah children. (2) the willing for the children to get the Islamic value and general science. (3) the willing for the children to be autonomous, brave and responsible children, (4) get the achievement, (5) the parents' necessity of a childcare for their children. Whereas, the extrinsic factors that cause the parents to choose the syariah based curriculum school SD Muhammadiyah Program Khusus Tinawas, Nogosari are: (1) the school location and environment (2 ) facilities and infrastructure, (3) vision and mission of school (4) the portion of religius education(5) the profile of the teachers (6) curriculum (7) alternative activity (8) discipline and clean school (9) scholastic skill (10)school fee (11) the achievement and the successful alumnus. The parents' expectation after their children graduated from SD Muhammadiyah Program Khusus Tinawas, Nogosari, is that the children will be the sholih and sholihah children,and be responsible for themselves and others.Keyword: motivation, parents, syariah based curriculum.